2020
DOI: 10.2144/btn-2019-0103
|View full text |Cite|
|
Sign up to set email alerts
|

Digital Droplet PCR and IDAA for the Detection of CRISPR Indel Edits in the Malaria Species Anopheles Stephensi

Abstract: CRISPR/Cas9 technology is a powerful tool for the design of gene-drive systems to control and/or modify mosquito vector populations; however, CRISPR/Cas9-mediated nonhomologous end joining mutations can have an important impact on generating alleles resistant to the drive and thus on drive efficiency. We demonstrate and compare the insertions or deletions (indels) detection capabilities of two techniques in the malaria vector mosquito Anopheles stephensi: Indel Detection by Amplicon Analysis (IDAA™) and Drople… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 21 publications
(33 reference statements)
0
17
0
1
Order By: Relevance
“…Digital droplet PCR drop-off assay reactions were performed as described in Carballar-Lejarazú et al ( 37 ).…”
Section: Methodsmentioning
confidence: 99%
“…Digital droplet PCR drop-off assay reactions were performed as described in Carballar-Lejarazú et al ( 37 ).…”
Section: Methodsmentioning
confidence: 99%
“…Since IDAA is based solely on fragment analysis, it can analyse editing outcomes in very complex polyploid/multi-allelic genomes, where the complexity would preclude sequencing-based indel analysis. Recent comparative analyses showed that IDAA, targeted NGS and digital droplet PCR assays provide very similar editing profiles for pools of cells with respect to size and frequency of indels ( 116 , 140 , 142 ). Thus, IDAA can provide quantitative determination of indels in complex editing profiles with single-base discrimination.…”
Section: Introductionmentioning
confidence: 99%
“…The translation of Cas9-mediated gene editing using adult injections have been demonstrated to efficiently support targeted mutagenesis in several species ( Chaverra-Rodriguez et al, 2018 ; Chaverra‐Rodriguez et al, 2020 ; Heu et al, 2020 ; Macias et al, 2020 ). This is supported by robust and affordable PCR and sequencing techniques ( Ran et al, 2013 ; Bell et al, 2014 ; Carballar-Lejarazú et al, 2020 ). Expansion of this will include both translation to more vector species and engineering the techniques for DNA and RNA delivery for heritable transgenesis and RNA interference methods.…”
Section: The General Impetus To Expand Genetic Engineering For Molecumentioning
confidence: 99%